Social skills of crack users accepted in therapeutic communities - Filho, Adauto Motta; Sousa, Andressa Aparecida Francisquini; Junior, Randolfo Santos; André, Julio Cesar; Santos, Loiane Leticia (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2020)
Objective: through this study, we aimed to assess the social skills of crack users in abstinence, by characterizing the demographic profile and identifying possible deficits in social skills. Method: with a convenience sample of 39 chemical dependents, with an average age of 40.7 years (± 10.48), hosted in therapeutic communities in the countryside of the state of São Paulo. The study is characterized as descriptive, transversal, with a quantitative delineation. Sociodemographic Questionnaire and Consumption Standard; Social Support Scale; Self-esteem Scale and the Social Skills Inventory (SSI) were the instruments utilized. Results: this study pointed out deficits in social skills in the general score (84.3%) of the participants and in the subcomponents of the social skills inventory. In the correlations of social skills and social support,affective (p < 0.0156) and emotional (p < 0.0299) factors were statistically significant, that is, the higher the social support indexes, the higher the social skills resources. The old age presented a negative correlation (p < 0,167) in social skills, that is, the older the age, the lower the social skills repertoire. Conclusion: this study highlights the relevance of social support to the chemical dependent as a factor of better social performance, allowing subsidies for...